Methodology: Preliminaries and background - Burt, C.; Caccetta, Louis (2018)
© 2018, Springer International Publishing AG. This chapter presents the basic concepts that are needed to develop mathematical models for the equipment selection problem in mining. These concepts include truck cycle time and a number of productivity measures for both trucks and loaders. The match factor, which is defined as the ratio of truck arrival rate to loader service time, is an important productivity indicator for trucks and loaders. The objective of the truck-loader optimisation problem is to minimise cost. So an important task in modelling is to establish an effective cost model. Equipment cost is dependent on many factors including purchase and salvage costs, maintenance costs and operating costs. In addition to providing some necessary background to equipment selection in mining, this chapter also provides a brief introduction to Linear and Integer Programming. Mixed Integer Linear Programming models provide the best option to accurately model and address the difficult equipment selection problems.